Prevalence and Risk Factors of Allergies in Turkey (PARFAIT): results of a multicentre cross-sectional study in adults - Kurt, E.; Metintas, S.; Basyigit, I.; Bulut, I.; Coskun, E.; Dabak, S.; Kalyoncu, A. Fuat (European Respiratory Soc Journals Ltd, 2009)
The Prevalence and Risk Factors of Allergies in Turkey (PARFAIT) study was planned to evaluate the prevalence of and risk factors for asthma and allergic diseases in Turkey. The present analysis used data from 25,843 parents of primary school children, obtained from a cross-sectional questionnaire-based study. A total of 25,843 questionnaires from 14 centres were evaluated. In rural areas, the prevalences asthma, wheezing, allergic rhinitis and eczema in males were: 8.5% (95% confidence interval (CI) 7.9-9.1%), 13.5% (95% Cl 12.8-14.2%), 17.5% (95% Cl 16.7-18.2%) and 10.8% (95% Cl 10.2-11.4%), respectively; and in females were: 11.2% (95% Cl 10.9-11.8%), 14.7% (95% Cl 14.3-15.1%), 21.2% (95% Cl 20.4-22.0%) and 13.1% (95% Cl 12.4-13.8%), respectively. In urban areas, the corresponding prevalences in males were: 6.2% (95% Cl 5.8-6.6%), 10.8% (95% Cl 10.3-11.3%), 11.7% (95% Cl 11.4-12.0%) and 6.6% (95% Cl 6.2-7.0%), respectively; and in females were: 7.5% (95% Cl 7.9-7.1%), 12.0% (95% Cl 11.7-12.3%), 17.0% (95% Cl 16.4-17.6%) and 7.3% (95% Cl 6.9-7.7%), respectively. Having an atopic first-degree relative or any other atopic diseases had significant effects on the prevalence of allergic diseases. Housing conditions, such as living in a shanty-type house, visible moulds at home and use of wood or biomass as heating or cooking material were associated with one or more allergic diseases. Although genetic susceptibility is strongly associated, country- and population-based environmental factors may contribute to increased prevalence rates of allergic diseases.
Keywords: Allergy; asthma; prevalence; risk factors; Turkey